Current aspects on vaccines and immunization in the dog and cat. Part II. Vaccines and vaccinations in the cat and postvaccinal complications - MYLONAKIS (Μ.Μ. ΜΥΛΩΝΑΚΗΣ), M. M.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; PLEVRAKI (Κ.Γ. ΠΛΕΥΡΑΚΗ), K. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The widespread use of vaccinations among the feline population has greatly contributed to the control of the most common infectious diseases, such as panleukopenia, upper respiratory viral diseases, leukemia virus infection, rabies, infectious peritonitis, chlamydiosis and Bordetella infection that threaten the health status or the life itself of the affected cats. Kittens having received colostrum can be vaccinated as soon as the 6th week of life, while the colostrum-deprived neonates two weeks earlier, provided that inactivated vaccines will be used. The induction of immunization and maintenance at protective levels through annual boostering are the main goals of all vaccination programmes applied to the cat. The unusual postvaccinal complications may include the 4 hypersensitivity types of reaction and the immunosupression reportedly related to some vaccine products (immunologic), the local reactions at the injection site, some reproductive problems, the appearance of the disease itself and the sarcomas (non-immunologic).